Новые для Черного моря свободноживущие нематоды - Сергеева, Н.Г. (Вестник зоологии, 1977)
When studying taxonomic composition of free-living Nematoda in some regions 0 f the Black sea nine species, unknown before for the given water body are found: Crenopharinx brevicaudatus 1970, Oncholaimellus mediterraneus Sch.-Stekhoven 1942, Parodontophora quadristicha (Sch.-Stekhoven, 1950), Viscosia minudonta Viti ello, 1970, Lonhomoeus iniquus Wieser, 1956, Metalinhomoeus typicus de M a n,
1907, Diplopettis onustus Wieser, 1956, Axonolaimus arcuatus Sch.-Stekhoven,
1950. Besides, the first four species are representatives of the genera first found in the Black Sea.